A emoção no contexto da prestação de serviços : um estudo aplicado junto a usuárias dos serviços de obstetrícia de um hospital público - Luchesi, Juliana Raquel de Souza (My University, 2014)
This study aims to identify ambivalent emotions (positive and negative) experienced by delivering mothers using obstetric services at the Caxias do Sul General Hospital (RS). The process of identifying such emotions may assist the Institution to set priority actions for employees? classification, risk and waste reduction and service quality improvement, as well as to increase the service users? satisfaction. The research methodology used is characterized as a qualitative research, with exploratory input, by means in-depth interviews with a semistructured approach, by applying a Basic Writing Questions Guide. It is worth noting that the data was analyzed and interpreted through analysis of content and, for complementary methods of research, direct observation and triangulation methods were used. The main results obtained from this work were: to understand the incidence of positive and negative emotions, that is, ambivalent emotions, simultaneously experienced by users of obstetric services at birth delivery, which, for this study, were fear and happiness/joy and, by analyzing such context, to propose directions towards maximizing positive emotions and minimizing negative emotions, resulting in the improvement of the perceived quality services provided.
Este estudo tem o intuito de identificar as emoções ambivalentes (positivas e negativas) vivenciadas no parto pelas usuárias dos serviços de obstetrícia do Hospital Geral de Caxias do Sul (RS). O processo de identificação de tais emoções poderá auxiliar a Instituição na definição de prioridades de ação, na qualificação dos funcionários, na redução de riscos e de desperdícios e no aumento da qualidade dos serviços prestados, bem como no incremento na satisfação das usuárias dos serviços. A metodologia de pesquisa adotada se caracteriza como uma pesquisa qualitativa, de caráter exploratório, com a realização de entrevistas individuais em profundidade, com uma abordagem semi-estruturada, mediante a aplicação de um Roteiro Básico de Questões. Cabe ressaltar que os dados foram analisados e interpretados por meio de análise de conteúdo e como métodos complementares de pesquisa foram realizadas a observação direta e a triangulação. Os principais resultados obtidos a partir da realização do trabalho foram: compreender a incidência de emoções positivas e negativas, ou seja, emoções ambivalentes, simultaneamente vivenciadas pelas usuárias dos serviços de obstetrícia no momento do parto, que para este estudo foram o medo e a alegria/prazer e, analisando tal contexto, a proposição de direcionamentos no sentido de maximizar as emoções positivas e minimizar as emoções negativas, repercutindo na melhoria da qualidade percebida dos serviços prestados.
Keywords: Hospital Geral de Caxias do Sul; Serviços de saúde - Administração; Comportamento do consumidor; Saúde - Planejamento; Consumer behavior; Emotions in services; Ambivalent emotions